2020
DOI: 10.21273/hortsci15344-20
|View full text |Cite
|
Sign up to set email alerts
|

Early Performance of Jujube Drying and Multipurpose Cultivars in the Southwestern United States

Abstract: Jujube cultivars have been imported into the United States for more than 100 years, but cultivar trials have been limited. To accurately recommend cultivars for each region, trials have to be conducted. We have set up jujube cultivar trials at the New Mexico State University (NMSU) Alcalde (2015, USDA hardiness zone 6a), Los Lunas (2015, 7a), and Leyendecker (2017, 8a) Centers with over 35 cultivars at each site with two replicates and a complete random block design. We reported the early performance of fresh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…In 2019, the average fruit weight and TSS content in Alcalde samples were less than samples from Las Cruces and Los Lunas. Previous study has also shown better jujube fruit quality-fruit size, average fruit weight, and TSS-from southern locations compared with northern New Mexico (Yao et al 2020).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In 2019, the average fruit weight and TSS content in Alcalde samples were less than samples from Las Cruces and Los Lunas. Previous study has also shown better jujube fruit quality-fruit size, average fruit weight, and TSS-from southern locations compared with northern New Mexico (Yao et al 2020).…”
Section: Discussionmentioning
confidence: 77%
“…The Alcalde weather patterns were very different between 2018 and 2019. The longterm average frost-free period is 146 d, and in the 10 years preceding the study was 150 d at Alcalde, NM (Yao et al 2020). There were only 122 frost-free days in 2019, from 24 May to 23 Sept, which is 3 to 4 weeks shorter than average.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…From 2011 to 2020, grafted plants were used for cultivar propagation, cultivar trials at NMSU (Yao et al, 2019(Yao et al, , 2020, or other locations. In 2014 and 2016, more than 40 cultivars were propagated for cultivar trials at the NMSU Sustainable Agriculture Science Center, the NMSU Agricultural Science Center in Los Lunas, NM, and the NMSU Leyendecker Plant Science Center in Las Cruces, NM (Yao and Heyduck, 2018;Yao et al, 2019Yao et al, , 2020. Because each cultivar had limited plants, grafting take rates were counted for all cultivars together instead of per cultivar.…”
Section: Methodsmentioning
confidence: 99%